Appendix 2.6: Selections from Philippines: Testimonies on Human Rights Violations - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
In addition to the appendix 2.5, these selections (Mercado and Dimanaran 1986, 66–69) show the variety—in terms of methods (torture to hamletting), victims (an individual clergyman to entire barangays), and geographic scope (from Luzon to Mindanao)—of victims of military abuses during the Marcos regime. It should be noted that all of these violations happened after martial law was supposed to have been lifted on 17 January 1981.